Imaging video plethysmography shows reduced signal amplitude in glaucoma patients in the area of the microvascular tissue of the optic nerve head - Tornow, Ralf-Peter; Kolar, Radim; Odstrcilik, Jan; Labounkova, Ivana; Horn, Folkert (Graefe's archive for clinical and experimental ophthalmology, 2021)
PURPOSE: To measure parameters of the cardiac cycle-induced pulsatile light absorption signal (plethysmography signal) of the optic nerve head (ONH) and to compare parameters between normal subjects and patients with different stages of glaucoma. PATIENTS AND METHODS: A recently developed video ophthalmoscope was used to acquire short video sequences (10 s) of the ONH. After image registration and trend correction, the pulsatile changing light absorption at the ONH tissue (excluding large vessels) was calculated. The changing light absorption depends on the pulsatile changing blood volume. Various parameters, including peak amplitude, steepness, time-to-peak, full width at half maximum (FWHM), and pulse duration, were calculated for averaged individual pulses (heartbeats) of the plethysmography signal. This method was applied to 19 healthy control subjects and 91 subjects with ocular hypertension, as well as different stages of primary open-angle glaucoma (17 subjects with ocular hypertension, 24 with preperimetric glaucoma, and 50 with perimetric glaucoma). RESULTS: Compared to the normal subjects, significant reductions (p < 0.001) in peak amplitude and steepness were observed in the group of perimetric glaucoma patients, but no significant difference was found for time-to-peak, FWHM, and pulse duration. Peak amplitude and steepness showed high correlations with RNFL thickness (p < 0.001). CONCLUSIONS: The presented low-cost video-ophthalmoscope permits measurement of the plethysmographic signal of the ONH tissue and calculation of different blood flow-related parameters. The reduced values of the amplitude and steepness parameters in perimetric glaucoma patients suggest decreased ONH perfusion and blood volume. This outcome is in agreement with results from other studies using OCT angiography and laser speckle flowgraphy, which confirm reduced capillary density in these patients. Registration site: www.clinicaltrials.gov , Trial registration number: NCT00494923.
Keywords: glaukom s otevřeným úhlem; Retinal plethysmography; Blood volume; Visual Fields; discus nervi optici; optická koherentní tomografie; zraková pole; Blood flow; Perfusion; lidé; Glaucoma; Intraocular Pressure; Plethysmography; Glaucoma, Open-Angle; Humans; Optic Disk; glaukom; Tomography, Optical Coherence; nitrooční tlak; pletysmografie